Personal Selling Strategy Analysis in Increasing Sales of Financing Products Based on Ethics Islam at PT Bank Sumut KCP Syariah SP.SY Kayu Besar Tanjung Morawa Deli Serdang, North Sumatra - Reza Rahmadani; Maryam Batubara; Nurul Inayah Siregar (LPPM UIKA Bogor, 2023)
The purpose of this research is to find out personal selling using the SWOT analysis method and to find out Islamic ethics in marketing activities at PT. Bank Sumut KCP Syariah Sp-Sy Kayu Besar. Personal selling is direct interaction with prospective buyers to influence purchasing decisions. So the method used is qualitative with SWOT analysis, interviews, documentation and observation used as data collection techniques. Primary data is used as the main data obtained from interviews with Account Officers and secondary data from books, journals and so on. PT.Bank Sumut KCP Syariah Sp-Sy Kayu Besar Tanjung Morawa is in quadrant I, which means that this bank has a strong opportunity to provide innovation and aggressive strategy recommendations, the ethics applied in PT.Bank Sumut KCP Syariah Sp-Sy Kayu Besar, namely honesty , responsibility, trust, satisfaction and ethics are in accordance with monotheism or are in accordance with Islamic ethics and personal selling in the bank has more advantages than weaknesses, this is what makes marketing run smoothly with the personal selling method.